Sistem Pendukung Keputusan Kelayakan Penerimaan Nasabah Menggunakan Metode Profile Matching - Anita Ahmad Kasim; Raziyan Dwi Pathan (Universitas Negeri Medan, 2020)
Abstract—PT Sarana Sulteng Ventura is one company that aims to provide loan capital is micro, small, and medium enterprises (UMKM) as a venture partner timed short or long to be able to stand on its own with loan capital that fits with the kind of effort that it takes for the customer. In providing venture capital loans, the company has some terms and conditions that apply. and the company still cultivate customer data manually so that it takes quite a long time. Then with this author makes the eligibility decision support system which will facilitate customer acceptance staff employees of PT Sarana Sulteng Ventura to pre-screen customer deserves a loan business capital to client or small medium enterprises. The researchers used a system that is web -based systems using the programming language PHP and MySQL into its data base processing and sublime text 2 as editor of programming languages. This research used the method of profile matching process to perform the calculation of assessments to help give the eligibility decision of acceptance the customer at PT. Sarana Sulteng Ventura city of Palu.